Geotechnical engineering of landfills proceedings of the symposium held at the Nottingham Trent University Department of Civil and Structural Engineering on 24 September 1998 - Dixon, N., Dr; Murray, E. J. 1949-; Jones, D. R. V. (Thomas Telford, 1998)
'Geotechnical Engineering of Landfills@ is a symposium designed to provide a forum for the presentation of recent developments in the design, construction and operation of landfills facilities. The papers presented in this volume bring together expertise and experience from industry, academia and the Environment Agency.